Factors Influencing Tax Compliance: A Literature Review - Christina VINCENT; Zauwiyah AHMAD; Yen Yen YIP (Communications of International Proceedings, 2020)
Studies on tax compliance have evolved over the years and it is highly important to analyse on the depth of the research findings and voids that could be filled for future researches. In general, past empirical studies warrants the importance of institutional factors, attitude, social factors and enforcement factors in raising tax compliance among the taxpayers. The inadequate sample and contradicting findings are the two major voids identified from the past studies to be addressed in the upcoming tax compliance studies.
Keywords: Tax Compliance; Factors; Taxpayers